Pengaruh Kuat Arus Dan Campuran Gas Argon – Co2 Pada Pengelasan Gmaw Terhadap Kekuatan Tarik Dan Impact Pada Baja Karbon Medium Fasa Ganda - Suyono, Eko Hendry; Irawan, Yudy Surya; Purnowidodo, Anindito (Jurnal Rekayasa Mesin, 2011)
The function of shielding gas is the most importance in gas metal arch welding, because it protected the oxidation from out side. Argon and CO2 are the shielding gas that often used, choosing the CO2 on mixing shielding gas for some reasons that is readystock , cheap and good penetration.The aim of this research are to know the influence of welding current and mixing shielding gas Argon – CO2 against tensile strength and impact strength on weld of medium carbon steel dual phase. The method of this research as follow AISI 1045 steel forged on temprature 900°C - 950°C then dual phase on 770°C holding tome 90 minutes as dependent variables. The Welding currents are 80A, 100A and 120A , mixing shielding gas , Argon – CO2 : ( 0 – 100%), (100% - 0) and (50% - 50%). Both are as independent variables. Tensile strength and impact strength are as fixed variables.From this research, It can be concluded that welding current and shielding gas have the influenced toward heat input and caused the weld metal fusion or unfusion. This situation influenced toward tensile strength and impact strength.It was prooved that on 80A for the 3rd shielding gas had defect (incomplete fusion and porosity) so the tensile strength and impact strength was very low. On 120A, ArCO2 mixing shielding gas had the highest tensile and impact strength because no defect in it, good fusion. Keywords: Dual phase steel, welding current, mixing shielding gas Ar – CO2, GMAW, tensile strength, impact strength